Przegląd metody leczenia i najczęstszych przyczyn amputacji otwartych i zamkniętych w obrębie kończyny górnej = Review of the methods of treatment and the most common causes of open and closed amputations within areas upper extremity - Katarzyna Pietkun; Joanna Siminska; Joanna Stocka; Karol Ogurkowski; Wojciech Hagner; Krystyna Nowacka (Kazimierz Wielki University, 2015)
Pietkun Katarzyna, Siminska Joanna, Stocka Joanna, Ogurkowski Karol, Hagner Wojciech, Nowacka Krystyna. Przegląd metody leczenia  i najczęstszych przyczyn amputacji otwartych i zamkniętych w obrębie kończyny górnej = Review of the methods of treatment and the most common causes of open and closed amputations within areas upper extremity. Journal of Education, Health and Sport. 2015;5(3):311-324. ISSN 2391-8306. DOI: 10.5281/zenodo.16770 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A311-324 https://pbn.nauka.gov.pl/works/554269 http://dx.doi.org/10.5281/zenodo.16770 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015.   PRZEGLĄD METODY LECZENIA I NAJCZĘSTSZYCH PRZYCZYN AMPUTACJI OTWARTYCH I ZAMKNIĘTYCH W OBRĘBIE KOŃCZYNY GÓRNEJ REVIEW OF THE METHODS OF TREATMENT AND THE MOST COMMON CAUSES OF OPEN AND CLOSED AMPUTATIONS WITHIN AREAS UPPER EXTREMITY Pietkun Katarzyna, Siminska Joanna, Stocka Joanna, Ogurkowski Karol, Hagner Wojciech, Nowacka Krystyna Katedra i Klinika Rehabilitacji Collegium Medicum UMK w Bydgoszczy Streszczenie W obecnych czasach obrażenia w obrębie rąk są dość często spotykanymi urazami w obrębie ciała. Często przyczynami amputacji są urazy powstałe podczas obsługi maszyn  zarówno maszyn rolniczych jak i maszyn w przemyśle rzemieślniczym. Każda amputacja jest zabiegiem odjęcia części kończyny lub jej całej. Nieważne jak dobrze będzie  dobrana proteza i długość uformowanego kikuta prawdziwej ręki nic nie zastąpi. Amputacje wiążą się nie tylko z utratą części własnego ciała, ale również z dużą zmianą postawy psychicznej. Słowa kluczowe: amputacja, przyczyny amputacji, powikłania po amputacji, amputacja zamknięta, amputacja otwarta.   Abstract   At the present time the damage within the hands are quite often common injuries within the body. Often the causes of amputation injuries are caused when handling machines both agricultural machinery and machinery in the craft. Each amputation is to become part of a limb or the entire. No matter how well chosen and the length of the prosthesis will be molded a genuine die-hand there is no substitute. Amputations are not only with the loss of parts of his own body, but also with a large change in mental attitude. Keywords: amputation, the causes of amputation, complications after amputation, closed amputation, open amputation.